THE JUDICIAL POLICY OF RATIO DECIDENDI REGARDING CORPORATE CRIMINAL LIABILITY TOWARDS JUST JUDGMENTS - Aryani, Fajar Dian; Pujiyono, Pujiyono; Sidharta, Sidharta (Indonesia Law Review, 2024)
Observing the workings of law in Indonesia is very intriguing, particularly regarding corporations in the era of globalization. In this context, the refunctionalization of law in the enforcement of corporate law is interpreted as a process of legal renewal and a part of a progressive and reformative legal political process. In this regard, the legal interpretation of corporate liability principles becomes the main focus of this dissertation. It appears that corporate liability, which is key to prosecuting corporations, still requires more serious efforts to be articulated in practical terms, leading to fair judicial decisions for both the corporation itself and the victims of corporate crimes. This situation drives the researcher to examine the issues of (a) How judges’ Ratio Decidendi interprets corporate liability, and (b) How the element of corporate fault should be interpreted in judges’ Ratio Decidendi to improve the regulatory provisions regarding corporate liability. The research method applied in this study is normative legal research. The statutory approach is used by reviewing all regulations related to the legal issue being studied, namely corporate liability. The conceptual approach is used as an argument to solve problems based on doctrines to better understand the basic ideas, legal concepts, and legal principles relevant to the issue. The method of interpretation often found in various criminal law literature is discussed. The research results affirm that legal interpretation and construction can be seen as ways for judges and other legal officers to discover the law. There is a difference in character between civil law and common law experts when discussing legal discovery. Thus, this study attempts to apply the use of the term Ratio Decidendi in the Indonesian criminal legal system, particularly in interpreting corporate liability.